The evolution of German's values since reunification - Sarah Necker; Andrea Voskort (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2013)
Exploiting the natural experiment of German reunification, we study whether having experienced socialism has an enduring effect on people's basic values. Using data from the German Socio-Economic Panel, we show that individuals that lived in the German Democratic Republic (GDR) assign different importance to six out of nine life goals. Our evidence suggests two reactions, adaption to policies/conditions in the GDR as well as switching to the opposite values. The strength of the reactions varies with East Germans' appreciation of reunification. Intergenerational transmission seems to contribute to the preservation of socialist in influence across generations; it does not differ between East and West Germany. We show that self-reported values are behaviorally relevant. Differences in values provide a possible explanation for persistent differences in behavior.
Keywords: D12; P26; J13; 330; endogenous preferences; socialism; intergenerational transmission